REGULASI ZAKAT DAN PENERAPAN ZAKAT PRODUKTIF SEBAGAI PENUNJANG PEMBERDAYAAN MASYARAKAT (Studi Kasus pada Baitul Mal Kabupaten Aceh Utara) - Nasrullah Nasrullah (State Institute of Islamic Studies (IAIN) Salatiga, 2015)
Regulation and application of productive zakat on Baitul Mal North Aceh have a significant role to improve the welfare of society, in education, religion, economics and so on. The purpose of this research is to explain the regulation of zakat and charity productive application as supporting the prosperity of society. This research is a field research, conducted in North Aceh Regency Baitul Mal with qualitative form. Data obtained from interviews and documentation, then analyzed with descriptive. The results showed that the presence of Baitul Mal North Aceh Regency bound by a number of regulations (Qanun). Application of productive zakat is to provide working capital loans based on qard al-Hasan to motivate well and maximum effort. This program gives significant impact to support the prosperity of the community.